Expression of Myeloid Antigen in Neoplastic Plasma Cells Is Related to Adverse Prognosis in Patients with Multiple Myeloma - Hyoeun Shim (BioMed Research International, 2014)
We evaluated the association between the expression of myeloid antigens on neoplastic plasma cells and patient prognosis. The expression status of CD13, CD19, CD20, CD33, CD38, CD56, and CD117 was analyzed on myeloma cells from 55 newly diagnosed patients, including 36 men (65%), of median age 61 years (range: 38–78). Analyzed clinical characteristics and laboratory parameters were as follows: serum β2-microglobulin, lactate dehydrogenase, calcium, albumin, hemoglobin, serum creatinine concentrations, bone marrow histology, and cytogenetic findings. CD13+ and CD33+ were detected in 53% and 18%, respectively. Serum calcium (P=0.049) and LDH (P=0.018) concentrations were significantly higher and morphologic subtype of immature or plasmablastic was more frequent in CD33+ than in CD33− patients (P=0.022). CD33 and CD13 expression demonstrate a potential prognostic impact and were associated with lower overall survival (OS; P=0.001 and P=0.025) in Kaplan-Meier analysis. Multivariate analysis showed that CD33 was independently prognostic of shorter progression free survival (PFS; P=0.037) and OS (P=0.001) with correction of clinical prognostic factors. This study showed that CD13 and CD33 expression associated with poor prognosis in patients with MM implicating the need of analysis of these markers in MM diagnosis.